Performance of beef heifers limit-fed growing diets containing alfalfa hay and wet corn gluten feed - Sean P. Montgomery; J.J. Sindt; T.B. Farran; N.J. Pike; C.M. Coetzer; H.J. LaBrune; A.M. Trater; R.D. Hunter; R.A. Stock; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2001)
Three hundred thirty-nine crossbred beef heifers were used in a 99-day growing study to identify optimum combinations of alfalfa hay and wet corn gluten feed (WCGF) in limit-fed growing diets. Diets contained 10, 20, or 30% ground alfalfa hay, and 0, 40, or 68% Sweet Bran® WCGF (dry basis) in a 3 x 3 factorial arrangement of treatments. An interaction occurred (P<0.05) between level of alfalfa hay and level of WCGF for both average daily gain and feed efficiency. Increasing the levels of alfalfa hay or WCGF reduced cattle performance, with the exception of the 30% alfalfa hay and 40% WCGF diet, which supported average daily gains similar (P>0.10) to diets containing 20 or 30% alfalfa hay and no WCGF. Feed efficiencies for the 30% alfalfa hay and 40% WCGF diet were better (P<0.05) than the diet containing 30% alfalfa hay and no WCGF. Dry matter intake as measured two hours after feeding increased linearly (P<0.01) with increasing levels of alfalfa hay, and decreased linearly (P<0.01) with increasing levels of WCGF. This study suggests that including WCGF at 40% of the diet (dry basis) can effectively replace steam-flaked corn in limit-fed diets containing 20 or 30% alfalfa hay.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Wet corn gluten feed; Alfalfa hay; Limit feeding; Growing